2001
DOI: 10.1034/j.1600-0714.2001.300608.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood oral pemphigoid: a case report and review of the literature

Abstract: Oral pemphigoid, defined as cicatricial pemphigoid limited to the oral cavity, is a clinical subset of cicatricial pemphigoid. Like cicatricial pemphigoid, it occurs mostly in middle-aged women and it is uncommon in children under 20 years of age. There are 11 cases of childhood cicatricial pemphigoid published previously in the English language literature, and four of them are oral pemphigoid patients. We present a case of the youngest oral pemphigoid patient reported yet. Because of the rareness of cicatrici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
0
19
0
2
Order By: Relevance
“…The disease usually affects middle-aged or elderly females (2,(7)(8)(9)(10)(11)12). It can manifest as erosions of the non-keratinized mucosa or desquamation of the There are only 13 cases of childhood MMP reported in the English literature (Table I), 6 of them diagnosed as oral MMP (4,9,10,(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The disease usually affects middle-aged or elderly females (2,(7)(8)(9)(10)(11)12). It can manifest as erosions of the non-keratinized mucosa or desquamation of the There are only 13 cases of childhood MMP reported in the English literature (Table I), 6 of them diagnosed as oral MMP (4,9,10,(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Sklavounou & Laskaris (15) studied III patients with one ofthe following diseases: MMP, pemphigus vulgaris or bullous pemphigoid (BP) presenting with DG, and found that 64% of them were consistent with (17). erythema mtiltiforme and plasma cell gingivitis, may also present with DG (2,12,16). erythema mtiltiforme and plasma cell gingivitis, may also present with DG (2,12,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eine ethnische oder geografische Prädilektion konnte bisher nicht nachgewiesen werden [4]. Es handelt sich um eine Erkrankung des älteren Menschen mit einem mittleren Erkrankungsalter von 64 Jahren, selten sind auch jüngere Patienten betroffen [5].…”
unclassified
“…It is a clinical manifestation common to several diseases (Endo et al, 2008a;Lo Russo et al, 2008;. It is seen mainly in adults, especially women, although rare cases have been observed in children (Barnett et al, 1981;Cheng et al, 2001;Leao et al, 2008;Lo Russo et al, 2009;Yih et al, 1998). Nisengard and Levine (1995) cited the following as the standard for the clinical appearance of DG: 1) Gingival erythema not resulting from plaque, 2) Gingival desquamation, 3) Other intraoral and sometimes extraoral lesions, and 4) Complaint of sore mouth, particularly after eating spicy foods.…”
Section: Introductionmentioning
confidence: 99%